Нелінійне керування вихідною напругою альтернативного джерела живлення в однофазній неавтономній мережі - Мисак, Тарас Володимирович (НТУ "ХПІ", 2018)
Об`єктом дослідження є джерело синусоїдальної напруги, яке має в своєму складі сонячну панель, перетворювач частоти з ШІМ та вихідним LC-фільтром і нелінійний однофазний вихідний трансформатор з додатковим фільтром на виході, підключений до однофазної неавтономної мережі споживача. Проведено пониження порядку афінної нелінійної сингулярно-збуреної системи диференціальних рівнянь, яка описує це джерело. Градієнтний метод отримання функції Ляпунова дав можливість застосувати нелінійну стратегію скалярного керування. Наводяться результати моделювання з урахуванням обмежень, які впливають на можливість реалізації отриманої стратегії нелінійного керування.

The object of the study is an autonomous source of sinusoidal voltage, which consists of photovoltaic panel, a bridge frequency converter with PWM, equipped with an output LC filter and a single-phase nonlinear output transformer with an additional output filter, which is connected to the non-autonomous grid. The nonlinearity of the magnetic system of the transformer is approximated by an odd function of the arc type. The substitution of variables made possible to develop a mathematical description of the circuit in the form of a nonlinear singularly perturbed system of differential equations. It is assumed that there is an attractive invariant surface, which makes it possible to reduce the order of the original system of equations. An analytical form of the equations of this surface in the form of a series in powers of a small parameter is obtained. A system of lower-order differential equations is obtained that is equivalent in some region to the original nonlinear singularly perturbed system. The non-linear reduced system is transformed to a form that has made it possible to apply the nonlinear feedback control strategies. The gradient method for obtaining the Lyapunov function allowed us to apply a nonlinear strategy of scalar control. A condition is set out in which the use of this function guaranteed the local asymptotic stability of this nonlinear system. The results of digital simulation are presented. The simulation was performed taking into account the limitations inherent in the real object of power electronics and affecting the possibility of technical implementation of the obtained control strategy. Local equivalency and isomorphism in the control strategies of full-length and reduced systems avoids the need to measure all variables in the space of states, which facilitates practical implementation. The possibility of reducing the impact of load jumps on the form of the output voltage has been checked, taking into account the constraints specific to real systems, has been verified using digital simulation.
Nonlinear control of the output voltage of a grid-connected alternative power source in a single-phase non-autonomous supply network
Keywords: вихідний LC-фільтр; нелінійний однофазний трансформатор; сингулярно-збурена система; градієнтний метод; функція Ляпунова; alternative power supply; output LC-filter; singularly perturbed system; nonlinear control; gradient method